The uses of globalization in the (shifting) landscape of Educational Studies - Tarc, Paul (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
The term ‘globalization’ does more than represent a set of material (and ideological) processes that have impacts on education and schooling. Additionally, ‘globalization’ operates as a conceptual lens or set of interventions, which is significantly impacting academic discourses in Education and in other disciplines. Not only has Globalization and Education (G&E) emerged as a new, trans-disciplinary field of Educational Studies, insights from this field and globalization studies more directly have impacted many other fields of Education. This paper summarizes major impacts of globalization on education and maps out a ‘first-wave’ G&E discourse by analyzing a small set of key texts published around the turn of the century. The paper distills key uses of globalization from this ‘first-wave’ G&E and more recent correctives to clarify the potential applications for—and implications of the ‘lens’ of—globalization for educational scholarship. Keywords: Globalization and Education, globalization, Educational Studies, methodology, deparochializing education